Insulation of a coumarin derivative with [1]rotaxane to control solvation-induced effects in excited-state dynamics for enhanced luminescence. Issue 25 (15th June 2022) - Russell, Go M.; Masai, Hiroshi; Terao, Jun
Abstract : A coumarin derivative bearing a [1]rotaxane structure with permethylated α-cyclodextrins suppressed unwanted solvation-induced effects and increased luminescent quantum yields in medium- and high-polarity solvents. Abstract : A coumarin derivative bearing a [1]rotaxane structure with permethylated α-cyclodextrins suppressed unwanted solvation-induced effects and increased luminescent quantum yields in medium- and high-polarity solvents. The non-radiative decay was suppressed by the twist in the π-conjugated system and the radiative decay was enhanced by the suppression of the polarity-induced structural changes.